H2 dynamics in the soil of a H2-emitting zone (São Francisco Basin, Brazil): Microbial uptake quantification and reactive transport modelling. (January 2020) - Myagkiy, Andrey; Brunet, Fabrice; Popov, Claudia; Krüger, Ricardo; Guimarães, Helena; Sousa, Rafaella Silveira; Charlet, Laurent; Moretti, Isabelle
Abstract: Sandy kaolinite-rich soils, collected in a H2 -emitting circular depression (ca. 500 m in diameter), located in the São Francisco basin (Brazil), were exposed to H2 gas concentrations in the 500–5000 ppm range for up to eight weeks. The samples were found to consume H2 at a rate of approximately 0.05–0.1 mmol H2 /soil kg/day due to the microbial activity. DNA extraction from these soil samples before and after H2 exposure, followed by Ribosomal Intergenic Spacer Analysis (RISA) and 16S rRNA gene amplicon sequencing, indicated that (i) the bacterial community is dominated by phyla that have been previously recognized to scavenge atmospheric H2, and (ii) H2 exposure leads to a significant modification of the bacterial community distribution. Measured H2 uptake rates were fitted to the integrated form of the Michaelis-Menten equation and were further implemented in a 1-D reactive transport model. The model simulates gas-soil interactions in a 1-m vertical soil column, assuming homogeneous distribution of H2 -consuming bacteria. The evolution of the H2 concentration in the unsaturated soil porosity along the column was simulated considering two different scenarios: a deep H2 source ( Case 1 ) and a biogenic surface source ( Case 2 ). It was shown that, in the case of diffusion-dominated H2 -transport as considered in this study, bacterial activity will control the amplitude of the H2 flux across the column. Moreover, we determined that bacterial activity can dramatically decrease the H2 concentration in the soil porosity, by a factor of two compared to the source concentration. According to the simulation, the time-resolved concentration data collected in the São Francisco depression [ Prinzhofer et al., 2019; International Journal of Hydrogen Energy ] are consistent with the combination of a deep ( Case 1 ) and a surficial biogenic ( Case 2 ) H2 source in this locality. Highlights: Soil samples of a H2-emitting structure (São Francisco Basin) uptake H2 ex-situ. H2 up-take rate of the soil samples is consistent with microbial activity. Laboratory H2 treatment changes the microbial taxonomic units abundance. Bacterial activity must consume a significant part of the H2 gas emitted at depth.